ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN PEDAGANG PASAR MANGLI KABUPATEN JEMBER - Nadir Muhammad kahfi Firdaus; Arfida Boedirochminarni; Muhammad Sri Wahyudi (Jurnal Ilmu Ekonomi, 2020)
Many factors influence the income of sellers. This research was aimed to examine the possible factors that affected the amount of income obtained by sellers of Mangli Market. This research was categorized as a descriptive research using quantitative method. This research was conducted in Mangli Market with 163 population of sellers. The samples in this research were 62 respondents taken by using slovin formula technique. Meanwhile the method of data collection were using questionnaires and conducting interview. The variables used included business capital, the duration of business practice, working hours and sellers’ income. The data analysis used was Multiple Linear Regression (OLS) with level of significance of 5%. The result show that the variable of capital significant positive effect of .021 the duration of business practice significant positive effect of .029 ) and working hours significant positive effect of .006 has simultaneously positive effect and significant to income. For individual, capital variable has no effect and significant at the income influence in Mangli Market  Mangli Village. Kaliwates  sub district, Jember districts